Endogenic intoxation in blood under conditions of combination pathology - immobilizational stress and adrenaline myocardial damage and correction of L-arginin - Lys, O. B.; Regeda, M. S. (Journal of Education, Health and Sport, 2019)
The syndrome of endogenous intoxication, which accompanies pathological processes, is caused by many mechanisms. Erythrocyte index of intoxication (EII) is one of the markers of endogenous intoxication. Medium Molecules (MSM) are products of catabolis m of endo- and exogenous proteins. The aim. of the study was to investigate the effect of L-arginine on the level of endogenous intoxication that occurs in the blood of white rats under the influence of acute immobilization stress and adrenal damage to the myocardium. Material and methods. The experiments were carried out on white male rats of the Vistar line weighing 180-200 g, which were divided into 3 groups of 10 animals (two experimental and one control). MSM254 MSM280 and EII in blood was determined. Results. The level of MSM254 increased by 1,3 times (p <0,05) and MSM 280 increased by 1,1 times (p <0,05) compared with the control group. Comparing the analysis of the results of the study of animals in the conditions of IP and APM after the use of the drug L-arginine for 5 days (experimental group 2), it was established that the decrease in the content of MSM254 in blood by 0,39 times (p <0.05) and MSM280 in blood on 0,31 times (p <0,05), respectively, in comparison with the experimental group number 1 before the treatment. The percentage of endogenous intoxication was also evaluated by the erythrocytic index of intoxication in the blood, which was determined on the 5th day after the simulations of IP and APM in rats prior to treatment. In particular, we have established an increase in EII by 0,99 times (p <0.05) against the control group. In the experimental group 2, which combined IC and APM, and the introduction of L-arginine occurred, on the 5th day the decrease in EII by 0,39 times (p <0.05) compared with the experimental group number 1.